Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T20:26:35+01:00



a)[(3x² -xy)*-2y]*3x=(-6x²y+2xy²)*3x=-18x³y+6x²y²=6x²y(3x+y)
b)(3x² -xy)*(-2y*3x)=(3x² -xy)*(-6xy)=-18x³y+6x²y²=6x²y*(-3x+y)
c)[3x² -xy+(-2y)]*3x=[3x² -xy-2y]*3x=9x³-3x²-6xy=3x*(3x²-x-2y)
d)(3x² -xy)*3x+(-2y)*3x=9x³-3x²y-6xy=3x*(3x²-xy-2y)
2010-03-17T20:33:09+01:00
Dane są wyrażenia algebraiczne: A: 3x² -xy
B: -2y C:3x

a) (A*B)*C
b)A*(B*C)
c)(A+B)*C
d) A*C+B*C

a)((3x²-xy)*-2y)*3x=(-6x²y-2xy²)*3x=-18x²y-6x²y²
b)(3x²-xy)(-2y*3x)=(3x²-xy)*-6yx=-18²yx³+6x²y
c)(3x²-xy -2y)*3x=9x³-3x²y-6xy
d)(3x²-xy)*3x+-2y*3x=9x²-3x²y-6xy